2021
DOI: 10.1177/23969873211056445
|View full text |Cite
|
Sign up to set email alerts
|

Preventive antibiotic therapy in acute stroke patients: A systematic review and meta-analysis of individual patient data of randomized controlled trials

Abstract: Introduction Infection after stroke is associated with unfavorable outcome. Randomized controlled studies did not show benefit of preventive antibiotics in stroke but lacked power for subgroup analyses. Aim of this study is to assess whether preventive antibiotic therapy after stroke improves functional outcome for specific patient groups in an individual patient data meta-analysis. Patients and methods We searched MEDLINE (1946–7 May 2021), Embase (1947–7 May 2021), CENTRAL (17th September 2021), trial regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…So far there is no sufficient evidence from clinical trials to demonstrate the effect of dysphagia screening protocols on the prevention of SAP ( 53 ). Meta-analyses of randomized trials have also failed to support the use of preventive antibiotic therapy to decrease the risk of SAP in acute stroke patients ( 54 , 55 ). Furthermore, only weak evidence exists about whether intensified oral hygiene care reduces the risk of SAP ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far there is no sufficient evidence from clinical trials to demonstrate the effect of dysphagia screening protocols on the prevention of SAP ( 53 ). Meta-analyses of randomized trials have also failed to support the use of preventive antibiotic therapy to decrease the risk of SAP in acute stroke patients ( 54 , 55 ). Furthermore, only weak evidence exists about whether intensified oral hygiene care reduces the risk of SAP ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preventive antibiotics had not shown any effect neither in reducing the incidence of stroke-associated pneumonia nor decreasing the mortality or improving the proportion of good outcomes within this field for the last decade. A systematic review ( 51 ) made an analysis of preventive antibiotics in patients with different risk score (A2DS2 or ISAN) and found risk scores did not significantly influence treatment response of preventive antibiotic therapy. However, few clinical trials have compared patients with different risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…There are several strengths in this meta-analysis. First, compared with previous studies, 7,8,29 this metaanalysis included more RCTs and sample size; thus, the confidence interval of the study and the heterogeneity between studies for each outcome were reduced. Second, we performed a subgroup analysis by time to the first dose of antibiotic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The previous Cochrane review and meta-analysis revealed that prophylactic antibiotics reduced the incidence of infections and urinary tract infections in post-stroke patients, but couldn't reduce the mortality rate and incidence of pneumonia. 7,8 However, a randomized controlled trial (RCT) recently published afterwards showed that prophylactic antibiotics decreased the mortality rate and the incidence of early-onset ventilatorassociated pneumonia in patients with acute stroke, 9 which were inconsistent with previous RCTs. [10][11][12] Therefore, prophylactic antibiotics in stroke patients remains a controversial issue.…”
Section: 6mentioning
confidence: 99%